P‐6: Student Poster: 2731ppi OLED Display with Low Power Consumption and Wide Viewing Angle Using OS/Si VLSI Process Technology. Issue 1 (28th June 2022) - Kimura, Kiyotaka; Tamatsukuri, Yuki; Shishido, Hideaki; Kobayashi, Hidetomo; Isa, Toshiyuki; Takeuchi, Toshihiko; Kunitake, Hitoshi; Kimura, Haijme; Yamazaki, Shunpei
Abstract : A 2731‐ppi OLED display was fabricated. Its source and scan drivers comprise Si transistors, and its pixel circuit comprises oxide semiconductor field‐effect transistors monolithically formed directly on the Si transistors.